Desenvolvimento de método cromatográfico limpo para a determinação de vitaminas lipossolúveis em alimentos explorando a cromatografia líquida de alta eficiência (CLAE) e ambientes micelares - Kienen, Vanessa (2007)
In the present work is proposed the separation and determination of fat soluble vitamins by using HPLC associated to micelar media, without usage of potentially toxic reagents as mobile phase. The determination of fat soluble vitamins in food, vitamin complex and similar samples were selected as application, always using a RP-18 column as stationary phase, which was temporary modified during the chemical analysis by the mobile phase constituents, increasing the applicability of the strategy and becoming possible the development of green analytical methods exploiting HPLC. The proposed method for determination of fat soluble vitamins was carried out by using 15.0 % (v/v) butyl alcohol, 3.00 % (w/v) SDS and 0.02 mol/L phosphate buffer, pH 7.00, temperature of 30.0º C, associated to a flow rate of 2.00 mL/min and a RP-18 as stationary phase. The analytical method is selective, sensitive, robust, simple, presents high analytical frequency, with retention times of 4.0; 9.6; 13.0 e 22.7 min, detection and quantification limits of 0.94: 0.89; 1.18 e 0.87 mg/L and 3.12; 3.00; 4.00 and 2.90 mg/L, respectively for D3, A, E and K1 vitamins with standard deviation of ca 5.0 %. When the proposed method was applied to real samples the obtained results were in agreement with those obtained by the conventional method.